Improving Students’ Reading Literacy and Character Education through the Folktales Reading Program and Qreatif.id Platform - Dewi Christa Kobis; Aditya Lapu Kalua; Andriyani Marentek (Yayasan Literasi Sains Indonesia, 2025)
This community service project aimed to improve reading literacy and character education among elementary students through the integration of Minahasan folktales and the digital platform Qreatif.id. Conducted at SD Katolik St. Nikolaus Talawaan, North Minahasa, the program adopted a participatory and descriptive approach involving 20 third-grade students and three teachers. The activities combined guided reading sessions using local folktales and digital literacy training through Qreatif.id. Data were collected through pre- and post-tests, classroom observations, and reflective interviews, and analyzed both quantitatively and qualitatively. The results revealed significant improvements in students’ reading fluency, comprehension, moral reasoning, and motivation. The number of fluent readers increased from 20% to 75%, comprehension accuracy rose to 85%, and moral understanding improved by over 50%. Teachers also demonstrated greater confidence in integrating digital media into instruction. This study concludes that combining local cultural materials with digital platforms provides an effective, contextualized, and engaging model for literacy learning while promoting cultural preservation and 21st-century digital competencies.